The Role of Information for Public Preferences on Education - Evidence from Representative Survey Experiments - Katharina Werner (ifo Institut – Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2019)
The aim of this doctoral project is an empirical analysis of questions concerning economics of education, in particular education policy. The first key aspect is the relationship between public opinion and the level of information of the population. As part of this, a first research project collected data on the similarities and differences in opinion of the American and German public. Respondents in both countries hold different views on a variety of issues, but they react to information in very similar ways. This suggests that the difference in policy outcomes between the U.S. and Germany is largely driven by institutional differences, rather than divergent preferences. A second research project focuses on public opinion on state spending for different areas of education. This research shows that providing respondents with the information that according to numerous studies, early childhood education has larger beneficial effects than other types of education spending raises support for increased spending for preschools. These information effects are driven by pervasive underestimation of positive effects of investment in early education. A second key aspect focuses on the question how to reduce the correlation between children's education outcomes and parental background. A first research project analyses the opinion of the adult population on structural reform of the education system that aims to increase educational opportunities for children from disadvantaged backgrounds. As it turns out, the majority of the German public perceives inequality in educational opportunities as problematic and supports reforms in this area. A second research project investigates divergence in educational aspirations of different socio-economic groups. Results show that information on earnings and unemployment rates of university graduates, as well as information on the tuition fees and student aid, raise the aspirations for their children's education less among respondents without university education than for respondents with university education. This suggests limited scope for information interventions to reduce the large gap in educational aspirations between children from different socio-economic backgrounds. – – Ziel des Promotionsprojektes ist es, Fragen der politischen Ökonomie der Bildung im Allgemeinen und der Bildungspolitik im Speziellen empirisch zu untersuchen. Ein erster Schwerpunkt ist der Zusammenhang zwischen der öffentlichen Meinung zu staatlichen Bildungsausgaben und dem Informationsstand der Wahlbevölkerung. In einem ersten Teilprojekt wurde die öffentliche Meinung der deutschen und der amerikanischen Bevölkerung im Vergleich darstellt. Es zeigt sich, dass Befragte in beiden Ländern zwar zum Teil unterschiedliche Positionen vertreten, auf bereitgestellte Informationen aber sehr ähnlich reagieren. Das spricht dafür, dass Unterschiede in den Institutionen eine größere Rolle bei der Erklärung von Politikunterschieden zwischen den Ländern spielen als abweichende Präferenzen. In einem zweiten Projekt liegt der Fokus auf der Meinung zu öffentlichen Ausgaben für verschiedene Bildungsinstitutionen in Deutschland. Hierbei zeigt sich, dass der Hinweis, dass laut wissenschaftlichen Studien frühe Investitionen besonders wichtig für die Zukunftschancen von Kindern sind, die Zustimmung zu höheren Ausgaben im frühkindlichen Bereich erhöht. Dieser Meinungsumschwung rührt von der weitverbreiteten Unterschätzung der positiven Effekte von frühkindlicher Bildung her. Ein zweiter Schwerpunkt ist die Fragestellung, wie die Abhängigkeit des Bildungserfolgs von Kindern von dem Bildungsniveau der Eltern reduziert werden kann. Ein erstes Teilprojekt untersucht die Meinung der Wahlbevölkerung zu strukturellen Reformen des Bildungssystems, die darauf abzielen Kinder aus bildungsferneren Schichten besonders zu fördern. Insgesamt zeigt sich, dass die Mehrheit der Deutschen die Chancenungleichheit in der Bildung als Problem sieht und Reformen in diesem Bereich befürwortet. Ein zweites Teilprojekt untersucht Unterschiede in den angestrebten Bildungsabschlüssen verschiedener sozialer Gruppen. Hierbei zeigt sich, dass Informationen über das spätere Einkommen und die zu erwartende Arbeitslosigkeit von Hochschulabsolventen, genauso wie Informationen über die Kosten des Studiums und finanzielle Studierendenförderung, die Bildungsziele von Eltern ohne universitäre Bildung weniger beeinflussen als die von Eltern mit Universitätsabschluss. Dies impliziert dass Informationsbereitstellung die gravierenden Unterschiede in den Bildungsambitionen zwischen Kindern aus bildungsnahen und bildungsfernen Elternhäusern nicht verringern kann.
Keywords: I22; I24; H52; J24; H75; D72; D83; P16; D30; H11; D63; D72; 330; education spending; inequality; information; survey experiments